Globalization and exclusionary urban growth in Asian countries - Amitabh Kundu; Debolina Kundu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper overviews the debate on the relationship between the measures of globalization, economic growth and pace of urbanization, and speculates on its impact on the quality of life and poverty in the context of Asian countries. After experiencing moderate to high urban growth for three to four decades since the 1950s, most of these countries have reported a significant deceleration. This questions the postulate of the epicentre of urbanization shifting to Asia. It also lends credence to the thesis of exclusionary urban growth, which is linked with the formal or informal denial of entry to poor migrants and increased unaffordability of urban space of the rural people. An analysis of the policies and programmes at the national and regional levels shows that these have contributed to the ushering in of this era of urban exclusion. The process of elite capture in the global cities has led to 'sanitization' and cleaning up of the micro environment by pushing out the current and prospective migrants and informal activities out of the city boundaries. Given the political economy of urban growth and the need to attract global and domestic capital into cities, governments would not interfere with 'elitist interests'. Asia, thus, is unlikely to go the same way as Latin America did in the second half of the last century. To absorb incremental labourforce outside agriculture, many of the large countries may, however, promote the small and medium towns that have unfortunately reported economic stagnation and deceleration in population growth. Furthermore, a few among the small and less developed countries are likely to experience high urban growth, largely due to foreign investment. This would impact on the geopolitical balance on the continent despite the fact that expansion in the urban and industrial base in these countries would not make a dent on macro-level aggregates.
Keywords: F5; R1; I0; 330; Water supply; perceptions; environmental health; transition; urbanization